(untitled) (Metallurgy and Foundry Engineering, 2019)
This paper presents the results of determining the effect of heat treatment after welding X8CrNiMoAl15-7-2 steel (commercial name: PH 15-7Mo steel) on the microstructure and texture of the welds. XRD studies showed the presence of the two phases in the welds of 15-7Mo steel; i.e., δ ferrite and austenite. Annealing at a temperature of 400°C/1 h and 550°C/1 h results in changes of the intensities for individual peaks derived from austenite and ferrite. Microstructure investigations carried out by LM and TEM indicated that the austenite and δ ferrite coexist in themicrostructure of 15-7Mo steel in as-welded condition. Annealing at a temperature range of between 400–620°C after welding causes small changes in the microstructure. The hardness of the welds after annealing in that temperature range increases.